Design of Integrated Corrosion E-module Vocational Context to Improve Critical Thinking Skills of Class X Students in Vocational High School - Wahyuni, Promes Sari; Haryani, Sri; Jumaeri, Jumaeri (International Journal of Active Learning, 2020)
Chemistry subjects as the basis of expertise are not placed by the needs of vocational subjects in every skill competency in vocational high school. The need for chemical materials in vocational high school for each skill competency is not the same for different skill competencies. Therefore, a vocational context integrated e-module design is needed to support chemistry learning activities and students for independent learning. The quality of teaching materials is measured by validity criteria, effectiveness, and practicality if teaching materials are used in the learning process. The development model used in this research is the 4D model (define, design, development, and dissemination). The data analysis technique uses qualitative and quantitative tests. Product development validation was carried out by media expert validators and chemical material experts, while the trial was conducted by 36 students of class X TKJ 2. The results of the analysis from the validator stated that the quality of learning material was in a very good category with a mean of 3.70 of material experts and 3.68 of media experts. The effectiveness of the e-module is shown by the increase in critical thinking skills of students with the achievement of N-gain of 0.57 in the medium category and classical completeness by 86.12%. The response of students to the practicality of using the e-module shows a result of 77.78% which belongs to the very good category and 22.22% which belongs to the good category. Based on the results obtained, it can be concluded that the student's worksheet developed to meet the criteria of valid, effective, practical, and can improve critical thinking skills.